Severe chest contusion: massive subcutaneous emphysema. Bilateral tension pneumothorax - Cazabán Perossio, Luis Alberto (Cirugía del Uruguay, 2020)
A case of severe chest contusion with the development of bilateral pressure pneumothorax, treated with bilateral thoracotomy, is reported upon.